Socially dangerous infringement as a reason for defense: certain aspects of criminal law interpretation - Lobanova, Lubov V.; Rozhnov, Alexey P. (Journal of the Belarusian State University. Law, 2019)
The article points out several interpretations of infringement actively used in current Criminal Code of the Russian Federation and analyzes the notion of socially dangerous infringement acting as a reason for justifiable defense according to art. 37 of the Criminal Code of the Russian Federation. Basing on the analysis of paragraphs 1–21 of this article and historical background of justifiable defense interpretation, the authors conclude that the most probable reason for defense is violent assault. However, this approach does not correspond to justifiable defense institution and narrows down the application of respective rights. This is why the authors approve amendments made by Supreme Court Plenum Resolution No. 19 of 27 September 2012, according to which the reasons for defense include not only assault but also any socially dangerous infringements, including involuntary or negligent ones. While noting the progress made by this resolution, the author indicate it would be more preferable to amend art. 37 of the Criminal Code of Russian Federation regulating the right to justifiable defense.